Investigation by photochemically-induced dynamic nuclear polarization and nuclear Overhauser enhancement 1H-NMR of the interaction between beta-endorphin and phospholipid micelles. - Zetta, L; Hore, P; Kaptein, R (1983)
The photochemically-induced dynamic nuclear polarization technique has been used to investigate the access of a photoexcited flavin dye to tyrosyl and histidyl residues in [Met]enkephalin and human and camel beta-endorphins, both alone and in the presence of n-dodecylphosphorylcholine micelles. The results indicate that the mode of binding of Tyr-1, but not of residue 27, is similar in the two endorphins and differs from that of Tyr-1 in [Met]enkephalin. In human beta-endorphin, accessibility and mobility of Tyr-27 are strongly reduced in the presence of lipid at physiological pH, whereas in camel beta-endorphin His-27 becomes immobilized only at high pH. Moreover, nuclear Overhauser enhancement experiments suggest a rigidifying influence of the peptide on the polar head groups of the micelles.